Effect of Negative Pressure on Proliferation, Virulence Factor Secretion, Biofilm Formation, and Virulence-Regulated Gene Expression of Pseudomonas aeruginosa In Vitro. (15th December 2016) - Wang, Guo-Qi; Li, Tong-Tong; Li, Zhi-Rui; Zhang, Li-Cheng; Zhang, Li-Hai; Han, Li; Tang, Pei-Fu
Abstract : Objective . To investigate the effect of negative pressure conditions induced by NPWT on P. aeruginosa . Methods . P. aeruginosa was cultured in a Luria–Bertani medium at negative pressure of −125 mmHg for 24 h in the experimental group and at atmospheric pressure in the control group. The diameters of the colonies of P. aeruginosa were measured after 24 h. ELISA kit, orcinol method, and elastin-Congo red assay were used to quantify the virulence factors. Biofilm formation was observed by staining with Alexa Fluor® 647 conjugate of concanavalin A (Con A). Virulence-regulated genes were determined by quantitative RT-PCR. Results . As compared with the control group, growth of P. aeruginosa was inhibited by negative pressure. The colony size under negative pressure was significantly smaller in the experimental group than that in the controls (p < 0.01 ). Besides, reductions in the total amount of virulence factors were observed in the negative pressure group, including exotoxin A, rhamnolipid, and elastase. RT-PCR results revealed a significant inhibition in the expression level of virulence-regulated genes. Conclusion . Negative pressure could significantly inhibit the growth of P. aeruginosa . It led to a decrease in the virulence factor secretion, biofilm formation, and a reduction in the expression level of virulence-regulated genes.